Toward an Open Trust Establishment Infrastructure for Future Network: Motivations, Models, and Technologies - Wang, Yiying; Kang, Xin; Li, Tieyan (IEEE access, 2024)
In the era of 6G, given the emergence of heterogenous devices, diverse network scenarios, along with future deployment of cutting-edge applications that require high computation ability, how to establish trust in such complex network environment has become a demanding task. Current trust establishment process mostly relies on certificates issued by certificate authority (CA) or reputation derived from interaction and behavior history. However, these approaches may not be applicable to 6G scenarios due to several reasons, including but not limited to insufficient adaptability, lack of openness and transparency, and limited scalability. Hence, this article mainly proposes a novel approach, which is based on a claim-attestation-evidence framework and leverages both blockchain and artificial intelligence (AI) to build trust in highly open and dynamic future networks. Meanwhile, we also provide an overview on current trust establishment models, discuss about the advantages of our proposed model and suggest certain parts of our current design for improvements that can be considered by future research.